ANALISIS STRATEGI PEMASARAN PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) UD. DIFIY PRINTING (STUDI PENELITIAN UMKM PERCETAKAN DI KAJEN MARGOYOSO PATI) - Balya Malkan; Gojali Supiandi (Journal of Research and Publication Innovation, 2024)
The aim of this research is to find out and analyze marketing strategies in micro, small and medium enterprises (MSMEs) Difiy Printing Kajen, to find out techniques and methods in marketing strategies and provide an overview of the results of implementing the marketing strategies that have been used. This research is descriptive qualitative research or describes something that is raised and researched. Using observation, interview and documentation methods. This research is field research which is reviewed and studied with the researcher going directly to look for primary and secondary data to be used as discussion in the research, then the research findings are presented and conclusions are drawn. The results of the research show that the marketing strategy for MSME Difiy Printing uses a marketing mix or 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) using STP techniques and methods (Segmentation, Targeting, and Positioning) which results The implementation of this strategy had an impact on increasing Difiy Printing's printing business income and received a positive response from the surrounding community. Based on the SWOT analysis through the IFAS AND EFAS tables, if outlined in the SWOT analysis diagram, the business position is in the second quadrant (II), where the internal strengths possessed by the Difiy Printing printer are prioritizing good and friendly service to customers and applying competitive prices to products. Offered as well as having clear distribution channels and carrying out promotional activities via social media.